Social Networking and Students’ Academic Performance: A Case Study on Malaysian Higher Education Institutions - Ng, Yee San (2013)
Social networks have been growing in rapid trend as well as widely spread to worldwide. There are millions of users have been implement social networks to build up communication, share information and create strong relationships. Majority of the youngsters in Malaysia even addicted to the virtual world of the SNSs. Nevertheless, questions remain unanswered regarding whether social networking sites (SNSs) will positively or adversely influence students’ academic performance. Therefore, this research aims to determine the usage influence of SNS such as time spent on SNS, multitasking, lacking of real communication and cognitive absorption on the students’ academic performance. Quantitative method, particularly survey questionnaires will be distributed to 320 of students from the age of 18 to 35 years old in Malaysian higher education institutions. Out of the 320 questionnaires, 250 were completed and returned. Meanwhile, SPSS software version 20 has been used to analyze the data collected from the respondents in order to meet the objective of this research. Reliability analysis and factor analysis was used to check the reliability and validity of the variables. As to check the relationship between the independent variables and dependent variable, multiple regressions were applied. The findings of this research pointed out that there is a significant association between multitasking, lacking of real communication and cognitive absorption towards students’ poor academic performance. Yet, it also indicates that there is no association between time spent on SNS and poor academic performance among students in Malaysian higher education institutions.